A Mitochondria‐targeted AIEgen Labelled with 18F for Breast Cancer Cell Imaging and Therapy. Issue 23 (20th October 2021) - Yu, Kaiwu; Zhou, Rui; Xu, Yangyang; Zhong, Yan; Qian, Shufang; Zhang, Honghai; Shi, Haibin; He, Qinggang; Mao, Zhengwei; Zhang, Haoke; Wei, Yen; Zhang, Hong; et al.
Abstract: A lack of efficient diagnostic tools for early and noninvasive diagnosis of breast cancer has restricted the clinical treatment effect. This problem might be addressed by the combination of aggregation‐induced emission (AIE) fluorescence imaging and positron emission tomography (PET) with the dual advantages of high resolution and easy operation, and unlimited penetration and high sensitivity. Here, a mitochondria‐targeted AIE luminogen (AIEgen) radiolabeled with 18 F was developed through a two‐step radiochemical reaction by virtue of a prosthetic group. The obtained 18/19 F‐Bz‐CP imaging probe was examined by in vitro cell uptake and cell proliferation inhibition in two breast cancer cell lines, showing that the probe can efficiently target and locate in the mitochondria through the analysis of fluorescence imaging and PET simultaneously. Additionally, the probe can induce cancer cell apoptosis with the half maximal inhibitory concentration (IC50) of 4.8 μM for MCF‐7 cells and 7.2 μM for T47D cells, indicating its potential application for breast cancer therapy. Abstract : A mitochondria‐targeted 18 F‐labelled AIEgen for highly sensitive breast cancer cell imaging and therapy is developed. Cell experiments reveal a highly efficient cell uptake of the probe by two breast cancer cell lines (MCF‐7 and T47D cells). Additionally, the probe shows potential therapy function for breast cancer cells through the induction of cancer apoptosis.